Nutritional and physicochemical profile of the pitahaya cultivated in the central coast of Peru - Obregón-La Rosa, Antonio José; Contreras-López, Eliana; Elías-Peñafiel, Carlos; Muñoz-Jauregui, Ana María; Yuli-Posadas, Ricardo Ángel; Cóndor-Salvatierra, Edwin Julio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Pitahaya, known as "dragon fruit", is an exotic fruit with excellent nutritional properties; however, the species from the Peruvian coast have been little studied. The objective of the present study was to determine the physicochemical and nutritional composition of two species of pitahaya Hylocereus undatus (Haw.) Britt and Rose (red pitahaya) and Hylocereus megalanthus (yellow pitahaya), cultivated in the central coast of Peru. Proximal analysis, physicochemical and mineral contents were determined by standardized methods. From the results found, the fiber content of red pitahaya (4.30 ± 0.75 g.100 g-1) and vitamin C (14.74 ± 0.53 mg.100 g-1) stand out. The macroelement with the highest proportion corresponded to potassium (215.83 ± 11.72 and 98.41 ± 5.54 mg.100 g-1, for red and yellow pitahaya, respectively). This was followed by phosphorus (28.70 ± 0.28 and 17.99 ± 1.48 mg.100 g-1, for red and yellow pitahaya, respectively) and magnesium (29.88 ± 0.53 and 16.09 ± 2.80 mg.100 g-1, for red and yellow pitahaya, respectively). Regarding the content of microelements, the contents of manganese (5.48 ± 0.1 mg.kg-1) and zinc (5.39 ± 0.25 mg.kg-1) for red pitahaya stood out; and in the case of yellow pitahaya, the highest values corresponded to iron (21.07 ± 0.18 mg.kg-1) and manganese (7.49 ± 1.12 mg.kg-1). The study concluded that red and yellow pitahaya fruits represent an important source of fiber, minerals and vitamin C and they can be used for the benefit of human health and nutrition.